PERAN KEBIJAKAN DIVIDEN DALAM MEMODERASI HUBUNGAN RASIO KEUANGAN DENGAN NILAI PERUSAHAAN - Putria Hafsadillah; Yusralaini Yusralaini; Devi Safitri (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
The purpose of this research was to analyze the effect of financial ratio on corporate value with dividend policy as moderation. Population on this research is all companies listed in Indonesia Stock Exchange (IDX) year 2015-2017. 108 companies selected using the purposive sampling method. Financial ratio used variable liquidity, solvency and profitability. The analysis method of this research is moderate regression analysis (MRA) by using SPSS 25 version. The result of this research shows that: liquidity has no significant effect on the corporate value, solvency and profitability has significant effect on the corporate value. Dividend policy has moderated relationship solvency and profitability with corporate value